Time to ACT : Realizing Indonesia's Urban Potential - Roberts, Mark (Washington, DC: World Bank, 2019)
In over 70 years since its independence, Indonesia has been transformed by urbanization, and within the next quarter of a century, its transition to an urban society will be almost complete. While urbanization has produced considerable benefits for Indonesians, urbanization has the potential to deliver more prosperity, inclusiveness and livability.